When do supervisors punish subordinates’ unethical pro-organizational behavior: Roles of moral identity and goal congruence with the group - Gao, Feng; Wang, Yao; Zhang, Jiaojiao (Frontiers in Psychology, 2023)
Given that unethical pro-organizational behavior (UPB) violates moral standards but benefits the organization at the same time, supervisors’ responses to this behavior could be equivocal although it is supposed to be punished. Previous research, however, has centered on antecedents of UPB, less is known about its consequences, especially how supervisors respond to subordinates’ UPB. Integrating social identity theory with social information processing theory, this paper aims to explain when supervisors perceive subordinate UPB in a negative way, and further engage in negative leading behaviors as punishments for UPB. Results of a multi-wave, multiple-source survey suggest that subordinates’ UPB is most negatively related to supervisors’ trust when supervisors’ moral identity is prominent and goal congruence with the group is low. Furthermore, results show that reduced trust ultimately elicits abusive supervisor behavior. These findings extend understanding of when and why supervisors punish rather than indulge subordinates who act in ethically questionable ways and provide important insights into supervisors’ leading behavior from a bottom-up perspective.